2016
DOI: 10.1021/acsnano.6b00877
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Contact Interfaces in Fully Printed Carbon Nanotube Thin-Film Transistors

Abstract: Single-walled carbon nanotubes (CNTs) printed into thin films have been shown to yield high mobility, thermal conductivity, mechanical flexibility, and chemical stability as semiconducting channels in field-effect, thin-film transistors (TFTs). Printed CNT-TFTs of many varieties have been studied; however, there has been limited effort toward improving overall CNT-TFT performance. In particular, contact resistance plays a dominant role in determining the performance and degree of variability in the TFTs, espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
98
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 51 publications
4
98
0
Order By: Relevance
“…The plot of R total vs. 1/( V GS  –  V T ) demonstrated that the extracted R D  +  R S was expected to be more accurate than the conventional R total extrapolation from the plot for R total vs. V GS because of the ease of fitting to the R D  +  R S value. Moreover, the CNT-TFTs with a higher CNT density tend to have lower combined contact resistances from the S/D electrodes, i.e., R D  +  R S , which is primarily attributed to an increased contact area between the CNT network film with a higher CNT density and the electrode 22 . A summary of the results of the averaged R D  +  R S from a total of 3–4 CNT-TFTs normalized to the width of the CNT network channel with different CNT densities is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plot of R total vs. 1/( V GS  –  V T ) demonstrated that the extracted R D  +  R S was expected to be more accurate than the conventional R total extrapolation from the plot for R total vs. V GS because of the ease of fitting to the R D  +  R S value. Moreover, the CNT-TFTs with a higher CNT density tend to have lower combined contact resistances from the S/D electrodes, i.e., R D  +  R S , which is primarily attributed to an increased contact area between the CNT network film with a higher CNT density and the electrode 22 . A summary of the results of the averaged R D  +  R S from a total of 3–4 CNT-TFTs normalized to the width of the CNT network channel with different CNT densities is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The functionalized wafer was then rinsed with DI water to remove the unattached monomers and blown dry thoroughly using N 2 gas 22 . Subsequently, the substrate was immersed in highly purified 99% semiconducting enriched CNT solution (concentration: 0.01 mg/ml, average diameter: 1.4 nm, average length: 1–2 µm, type of purification: density gradient ultracentrifugation, provided by NanoIntergris, Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Field effect transistors (FETs) based entirely on carbon nanotubes (CNTs) have several advantages such as simple device design, improved contact at the channel-to source(S)/drain(D) interface, good optical transmittance and excellent mechanical flexibility 39 . The use of CNTs as electrodes instead of metallic electrodes provides not only mechanical flexibility and transparency but also good electrical contacts to an CNT channel due to ideally the similar work function of the CNT electrodes and channel 7, 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of CNTs as electrodes instead of metallic electrodes provides not only mechanical flexibility and transparency but also good electrical contacts to an CNT channel due to ideally the similar work function of the CNT electrodes and channel 7, 10 . Improved electrical contact at the channel-to-S/D interface results in a small contact resistance, which could lead to high on-current 3 . Various approaches such as transferring, printing and self-assembly process have been developed to fabricate high performance CNT-based transistors 4, 5, 79, 1116 .…”
Section: Introductionmentioning
confidence: 99%